New data on the paleobiology of the Gravettian individual L2A from Cussac cave (Dordogne, France) through a virtual approach. (August 2017) - Guyomarc'h, Pierre; Samsel, Mathilde; Courtaud, Patrice; Mora, Pascal; Dutailly, Bruno; Villotte, Sébastien
Abstract: One of several elements making Cussac cave an exceptional site is the preservation of many prehistoric human remains lying on the ground, including an individual in a bear nest (Locus 2) in ventral decubitus, subject L2A. The protected status of the site does not allow for excavations or direct manipulation of the remains, at least for the near future. Thus, the tools of virtual anthropology were employed to further study this individual, after preliminary analyses in situ in 2014 raised several questions on its biological characteristics. A high-resolution 3D photogrammetric record of Locus 2 allowed for the virtual reconstruction of the ossa coxarum and cranium to be measured in TIVMI. Metric data from the ossa coxarum were used to apply the DSP, which indicated a male sex assessment for the left side. The linear variables and log shape ratios extracted from the cranium were compared to a reference sample composed of 46 Upper Paleolithic (UP) subjects. The cranial morphology of L2A is closer to the male variability for the UP, but displays an unusual pattern, with a short cranial height and a wide splanchnocranium. The biological peculiarities of this subject are discussed with regard to Gravettian funerary practices and the depositional context of Cussac cave. Highlights: Remains of Cussac L2A Gravettian subject are investigated through photogrammetry. Ossa coxarum morphology indicates a male sex with the DSP. The cranial pattern is peculiar when compared to Upper Paleolithic individuals. Virtual anthropology provides additional information on Gravettian biology.